The effect of training in minimalist running shoes on running economy - Ridge, S. T.; Standifird, T.; Rivera, J.; Johnson, A. W.; Mitchell, U.; Hunter, I. (Journal of Sports Science & Medicine, 2015)
The purpose of this study was to examine the effect of minimal-ist running shoes on oxygen uptake during running before and after a 10-week transition from traditional to minimalist running shoes. Twenty-five recreational runners (no previous experience in minimalist running shoes) participated in submaximal VO2 testing at a self-selected pace while wearing traditional and minimalist running shoes. Ten of the 25 runners gradually tran-sitioned to minimalist running shoes over 10 weeks (experimental group), while the other 15 maintained their typical train-ing regimen (control group). All participants repeated submaxi-mal VO2 testing at the end of 10 weeks. Testing included a 3 minute warm-up, 3 minutes of running in the first pair of shoes, and 3 minutes of running in the second pair of shoes. Shoe order was randomized. Average oxygen uptake was calculated during the last minute of running in each condition. The average change from pre- to post-training for the control group during testing in traditional and minimalist shoes was an improvement of 3.1 ± 15.2% and 2.8 ± 16.2%, respectively. The average change from pre- to post-training for the experimental group during testing in traditional and minimalist shoes was an improvement of 8.4 ± 7.2% and 10.4 ± 6.9%, respectively. Data were analyzed using a 2-way repeated measures ANOVA. There were no significant interaction effects, but the overall improvement in running economy across time (6.15%) was significant (p = 0.015). Run-ning in minimalist running shoes improves running economy in experienced, traditionally shod runners, but not significantly more than when running in traditional running shoes. Improve-ment in running economy in both groups, regardless of shoe type, may have been due to compliance with training over the 10-week study period and/or familiarity with testing procedures.